2020
DOI: 10.1016/j.celrep.2020.108549
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Repair-Supportive Mesenchymal Cell Population during Airway Epithelial Regeneration

Abstract: Highlights d The mesenchymal niche is critical for airway epithelial regeneration d b-catenin signaling and FGF10 production are pivotal for proper repair after injury d RSMCs, which are distinct from ASMCs, emerge after clubcell depletion d RSMCs display high potential to support bronchiolosphere formation in vitro

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 36 publications
2
42
0
Order By: Relevance
“…Our knowledge about the sources of FGF10 in this context has been evolving. FGF10 was first described to be expressed by airway smooth muscle cells (ASMCs) ( Volckaert et al, 2011 ), whereas more recent work identified a peribronchiolar mesenchymal population capable of producing FGF10 during the repair process, which is not derived from the ASMCs ( Moiseenko et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our knowledge about the sources of FGF10 in this context has been evolving. FGF10 was first described to be expressed by airway smooth muscle cells (ASMCs) ( Volckaert et al, 2011 ), whereas more recent work identified a peribronchiolar mesenchymal population capable of producing FGF10 during the repair process, which is not derived from the ASMCs ( Moiseenko et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of the repair process, Fgf10 deletion in peribronchial mesenchymal cells leads to impaired repair following injury to the bronchial epithelium using naphthalene ( Volckaert et al, 2011 ; Moiseenko et al, 2020 ). On the other hand, overexpression of Fgf10 reduces the severity of lung fibrosis in bleomycin-induced mice ( Gupte et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fgf10 inactivation leads to lung agenesis [19] while Fgf7 null mice are viable and display no obvious lung phenotype [20]. Changes in endogenous Fgf10 expression has been correlated with disease progression and/or repair after lung injury both in mice and humans [21][22][23]. Evidence for such a role for Fgf7 in the embryonic or adult lung in human or mice are still lacking in spite of the fact that Fgf7 was discovered 7 years before Fgf10 [24,25].…”
Section: Discussion Rmc-sca1 Pos Fgf10 Pos Are Different From the Rmc-sca1 Pos Axin2 Posmentioning
confidence: 99%
“…Here, we provide a detailed protocol for culturing airway organoids, or bronchiolospheres, which provide an assessment of the ability of mesenchymal cells to support club-cell growth. For complete details on the use and execution of this protocol, please refer to Moiseenko et al. (2020) .…”
mentioning
confidence: 99%
“…For complete details on the use and execution of this protocol, please refer to Moiseenko et al. (2020) .…”
mentioning
confidence: 99%